Wireless access control - Teck Ping, Lee (2005)
Wireless, a technology introduced to replace the wired connection is widely used in today's work and industiy segment.However,in wireless technology,user from outside are allowed to access the internet and private network in a wireless network area, as they are not authenticated.Here,The WachSpot system,a prototype developed to controlling the wireless user's access by using the login authentication technique and a small wireless hotspot architecture created for the implementation of the prototype.HTML and PHP programming languages have been chosen to design the system while Microsoft Access for storing the user data.A study has been conducted on types of access points,IP address and architecture that are suitable for WachSpot implementation.In order to make the development of system completed,planning has been prepared,the data collected, software and hardware requirements needed were analyzed to come out with the use case model and system architecture consist of user, access point and access server only.All interfaces have been generated by using the HTML and PHP while the implementation of system has been completed before the prototype is tested.The success of implementation and development of this project is expected to increase the security in wireless network by requiring the user to register a new account and login through the system to access the internet.